2019
DOI: 10.1016/j.jtumed.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Gender variations in social media usage and academic performance among the students of University of Sharjah

Abstract: Objective Social media usage is considered one of the most common activities among university students that could impact their daily lives. There is a great variation of the level of this impact depending on gender and some other factors. The impact of social media usage on academic performance is not known. This study aims to evaluate gender differences amongst students at the University of Sharjah (UoS) for predicting the impact of social media usage on their academic performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
60
6
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 15 publications
12
60
6
2
Order By: Relevance
“…We detected a significant difference in the mean values of Facebook addiction score between male students (6.29 ± 5.35) and female students (5.45 ± 4.95) (p= 0.025) which is in line with previous studies that cited male gender to be more addicted to Facebook (Çam & Işbulan, 2012) and social media in general (Alnjadat, Hmaidi, Samha, Kilani, & Hasswan, 2019). Furthermore, similar to the study by Błachnio et al, 2015, who identified male and young age to be significant predictors of Facebook intrusion, we also noted male gender and young age to be significant predictors of Facebook use.…”
Section: Discussionsupporting
confidence: 90%
“…We detected a significant difference in the mean values of Facebook addiction score between male students (6.29 ± 5.35) and female students (5.45 ± 4.95) (p= 0.025) which is in line with previous studies that cited male gender to be more addicted to Facebook (Çam & Işbulan, 2012) and social media in general (Alnjadat, Hmaidi, Samha, Kilani, & Hasswan, 2019). Furthermore, similar to the study by Błachnio et al, 2015, who identified male and young age to be significant predictors of Facebook intrusion, we also noted male gender and young age to be significant predictors of Facebook use.…”
Section: Discussionsupporting
confidence: 90%
“…4 The present study was conducted to see the impact of social media on dental treatment choices. In the present study a total of 477 subjects participated and amongst them, 303 (63.5%) were females which is in agreement to the study conducted by Alnjadat et al 7 In a survey, Hanna Krasnova et al concluded that due to their emotional volatility, females use social media platforms more than males (they like to keep close ties and gain social information). 8 In the present study less than half (38.2%) of participants were following a dentist or a dental clinic on social media which is in contrast with a study conducted by Awdah et al where 53.3% were following a dentist on social media.…”
Section: Discussionsupporting
confidence: 91%
“…Rollero, Daniele and Tartaglia (2019) reveal that men are more committed to the use of social media than women which could be attributed to their perception on the influence of social media on their academic performance. This finding goes in line with Misra, Dangi and Patel (2015) and Alnjadat, Hmaidi, Samha, Kilani and Hasswan (2019). In the finding of Amadi and Ewa (2018), there is divergence between male and female university students on their use of social media.…”
Section: Introductionsupporting
confidence: 80%